ANALISIS EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH KOTA BATAM NO 10 TAHUN 2009 DALAM PENATAAN DAN PEMBINAAN PASAR - Meysi Ansari Br Ginting; Lubna Salsabila; Etika Khairina (stiatabalong.ac.id, 2023)
Batam City Regional Regulation (Perda) No. 10 of 2009 is one of the regulations that has the aim of regulating and facilitating the regulation and development of markets in the Batam City area. Structuring and fostering markets is an important step in regulating trade and commercial activities in a city or area in order to create a more orderly, safe, clean, and comfortable environment for traders and the general public. The purpose of this study is to assess how good the Batam City Regional Regulations are. Number 10 of 2009, which regulates the development and arrangement of markets in Batam City, has been implemented. The research method used is a descriptive approach, namely qualitative research. Data was collected through field observations, interviews conducted with the industry and trade office of the city of Batam and with stakeholder traders, and document analysis. Field observation by visiting various markets in Batam City to observe the implementation of local regulations and structuring practices as well as market training. The data obtained were then analyzed descriptively. The results show that the enactment of Batam City Regional Regulation No. 10 of 2009 has had a beneficial impact on market management in Batam City. Better store design, public facilities, and more organized market infrastructure are signs of better organization. The rules also include training sessions for traders, which provide them with a technical understanding of how to run a company and an understanding of the necessary laws. Through these instructions, the standard of the study also uncovered a number of issues that needed to be addressed for this law to be successfully implemented, including effective monitoring, coordination between various relevant authorities, and regulatory compliance by all parties involved. Therefore, there is a need for ongoing efforts to ensure that regulations are applied consistently and to increase the effectiveness of coaching the trading community.